ROMANCE OF THE THREE KINGDOMS WARS AND HEROES - Luo, Guanzhong; Loh, Pauline; Yee, Patrick (Singapore : WS Education, 2022)
In the midst of war, heroes rise up. But heroes come in different shapes and sizes. Some are good with swords and spears, like Zhao Yun. Others use their brains, like Zhuge Liang. Although men grow old, a hero will always be a hero, like the elderly Huang Zhong. In the second book of the Romance of the Three Kingdoms series, learn about the heroes of ancient China!
Keywords: English fiction; War -- Juvenile fiction; Superhores -- Juvenile fiction; China -- History -- Three Kingdoms, 220-265 -- Juvenile fiction